THE MEANING OF PREDATORY PRICING IN SOCIAL COMMERCE (A PHENOMENOLOGICAL STUDY ON CONVENTIONAL UMKMS IN SURABAYA) - Maharani, Aisyah; Merry Frida; Bambang Sigit Purnomo (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2024)
This research aims to examine the phenomenon of predatory pricing in social commerce and its impact on conventional UMKMs in Surabaya. The data shows that the use of social media and online shopping platforms by the public is very high, but there are allegations of predatory pricing that threaten conventional UMKMs. This practice can result in a decrease in revenue, business losses, and even bankruptcy for UMKMs. Although the number of UMKMs using social commerce has increased, the utilization of technology by conventional UMKMs is still low. This gap highlights the importance of this research in understanding the meaning of predatory pricing in social commerce for conventional UMKMs. Proving this practice is difficult due to the lack of adequate data and information. Intense business competition can also lead to bias in interpreting the meaning of predatory pricing. Therefore, this research adopts a qualitative method with a phenomenological approach to explore the meaning of predatory pricing in social commerce among conventional UMKMs in Surabaya. The study is expected to provide a clearer understanding of this phenomenon and contribute to creating a healthier business environment.